PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL BERBASIS TEKNOLOGI AUGMENTED REALITY PADA PEMBELAJARAN MATEMATIKA MATERI BANGUN RUANG DI KELAS V SEKOLAH DASAR - Yuliana, Peni; Ningsih, Yarisda; Zainil, Melva; Nisa, Sahrun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The limited use of interactive digital learning media in Mathematics instruction, particularly on the topic of three-dimensional geometry for fifth-grade elementary school students, has become a significant challenge. Learning activities are still dominated by lecture-based methods and conventional instructional media, making it difficult for students to understand abstract geometric concepts. This study aimed to develop a digital learning media based on Augmented Realitytechnology that is valid, practical, and effective. This research employed the Research and Development(R&D) method using the ADDIE development model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects included a language expert, a material expert, a media expert, a fifth-grade teacher, and fifth-grade elementary school students. Data were collected through observations, interviews, questionnaires, and tests, while the data were analyzed quantitatively using percentage analysis for validity and practicality, as well as the N-Gain test to determine effectiveness. The findings revealed that the developed media achieved an average validity score of 95.7%, categorized as highly valid. The practicality assessment conducted by teachers and students indicated that the media was highly practical, while the effectiveness test demonstrated an improvement in students' learning outcomes based on the pre-test, post-test, and N-Gain analysis results. The Augmented Reality-based digital learning media was able to present three-dimensional geometric objects interactively, enabling students to understand concepts more easily, enhancing their learning motivation, and creating a more engaging and student-centered learning experience. Therefore, the developed media was proven to be valid, practical, and effective, making it suitable as an alternative instructional medium for teaching three-dimensional geometry in fifth-grade elementary school Mathematics.